Identification and characterisation of superior onion line for high-temperature condition - Abhilash Kavalgi; Sabina Islam; S.K. Lal; B.S. Tomar (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Onion is a cool-season crop and the development of high temperature tolerant varieties will help in alleviating ‘onion - crises’. A total of 7 onion genotypes were exposed to constant temperature of 25, 30, 35, 40 and 45°C under in vitro and grown under increasing temperature from March to May to study the impact of high temperature on morphological traits and bulb yield. The genotypes responded differently and high temperature led to decline in germination (%), survival days, seedling length and weight. Sel. 140 exhibited less decline compared to other genotypes. The drastic reduction of germination percentage was recorded at higher temperature of 40 and 45°C. The highest seedling vigour index of 2062 was exhibited by Sel. 140. The highest germination (%) was recorded in March sowing in genotype Sel. 140 (90.3) and least in May sowing in genotype Sel. 417 (65.3). High temperature resulted in a significant reduction in vegetative growth traits and yield traits. Agrifound Dark Red and Sel. 140 were found promising for high temperature tolerance. The high amount of variability suggests scope for improvement and gradual genetic drift is possible to develop onion varieties suitable for high temperature condition.